Abdominal Pseudocyst, a Rare Complication of Shunting Procedure: A Case Report - Dehneh, Younes; Al Dabbas, Mohannad; Dahamou, Mohammed; Kada, Amine; Khoulali, Mohammed; Oulali, Noureddine; Moufid, Faycel (Jordan Medical Journal, 2024)
The use of the peritoneal cavity for cerebrospinal fluid (CSF) absorption was introduced in 1905. Since then, the ventriculoperitoneal shunt has been one of the most commonly performed surgeries to treat hydrocephalus. Abdominal pseudocysts are relatively rare abdominal complications due to the insertion of a ventriculoperitoneal shunt. Their incidence varied between 0.33 and 6.8%. We report a young boy with a history of hydrocephalus treated by ventriculoperitoneal shunt he admitted to our department presenting with abdominal pseudocyst revealed by abdominal pain and headache. He underwent surgery, where shunt was externalized and the pseudocyst was excision. The shunt was reinserted after the infection was eradicated in the atrium.